Harmful algal blooms during 2008-2010 in the Gulf of Nicoya, Costa Rica - Calvo-Vargas, Emilia; Berrocal-Artavia, Karen; Boza-Abarca, Jorge (Revista Ciencias Marinas y Costeras, 2016)
Harmful Algal Blooms (HABs) events were analyzed in this study at four monitoring stations in the Gulf of Nicoya between January 2008 and December 2010. Water samples were collected at 1 and 5 m deep during each HAB event. Furthermore, the following physicochemical parameters were measured in situ: Secchi disk depth, temperature, salinity, dissolved oxygen, and saturation percentage of oxygen in water. Radiation and precipitation data was provided by the National Meteorological Institute of Costa Rica. The concentration of dominant microalgae and associated species was determined. A total of 11 events were recorded, 72.7% during rainy season and 27.3% during dry season, most of them during the La Niña atmospheric phenomenon. Dominant species included the following dinoflagellates; Alexandrium monilatum, Levanderina fissa, Cochlodinium polykrikoides and Prorocentrum minimum, as well as diatom Skeletonema costatum and cyanobacterium Trichodesmium erythraeum. The most frequent associated species were dinoflagellates Dinophysis caudata, Prorocentrum micans, Tripos fusus, Tripos furca and Protoperidinium conicum. HABs in the Gulf of Nicoya were more frequent during the rainy season, probably due to the contributions of the Tempisque, Barranca and Grande de Tárcoles rivers to the estuarine system. This seasonality, together with the alterations caused by El Niño and La Niña atmospheric phenomena, determined the development of HABs in the Gulf of Nicoya during the study period.